High Prevalence and Gender-Related Differences of Gastrointestinal Manifestations in a Cohort of DM1 Patients: A Perspective, Cross-Sectional Study - Perna, Alessia; Maccora, Daria; Rossi, Salvatore; Nicoletti, Tommaso Filippo; Zocco, Maria Assunta; Riso, Vittorio; Modoni, Anna; Petrucci, Antonio; Valenza, Venanzio; Grieco, Antonio; Miele, Luca; Silvestri, Gabriella (Frontiers in Neurology, 2020)
Myotonic dystrophy type 1 (DM1, MIM #160900), that is the most common muscular dystrophy among adults, is a multisystem disorder, which affects, besides the skeletal muscle, several other tissues and/or organs, including the gastrointestinal apparatus, with manifestations that frequently affects the quality of life of DM1 patients. So far, only few, mainly retrospective studies evaluated this specific topic in DM1, so we performed a perspective study, enrolling 61 DM1 patients who underwent an extensive diagnostic protocol, including administration of a validated patient-reported questionnaire about GI symptoms (GSRS), laboratory tests, liver US scan and intestinal permeability assay, in order to characterize frequency and assess correlations regarding specific gastrointestinal manifestations with demographic or other DM1-related features. Our results confirm the high frequency of various gastrointestinal manifestations, with the most frequent being constipation (45,9%). γGT levels were pathologically increased in 65% of DM1 patients and GPT in 29.82%; liver ultrasound studies showed steatosis in 34,4% of patients. Significantly, 91,22% of DM1 patients showed signs of altered intestinal permeability at the specific assay. We documented a gender-related prevalence and severity of gastrointestinal manifestations in DM1 females compared to DM1 males, while males showed higher serum GPT and γGT levels than females. Correlation studies documented a direct correlation between severity of muscle weakness estimated by MIRS score and γGT and alkaline phosphatase levels, suggesting their potential use as biomarkers of muscle disease severity in DM1.